(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The external auditor has major role in helping financial institutions in cases of financial disaster through the procedures followed to verify the measurement and disclosure of the effects of the financial disaster as research aims to assist the external auditor in the audit disclosure of financial disaster addition to the preparation of a proposed program can tamper abroad guided by when he express an opinion to the financial statements of the administration, which is under financial disaster they found the conclusions, including: weakness followed banking procedures by the bank management with respect to financial disaster, and the lack of adequate disclosure of data relating to financial disaster, and gave researchers a set of recommendations, including: the need to develop and adopt a set of precautionary measures that contribute to the disclosure of financial disaster and predict them to occur, and that is the responsibility of the banking departments direction of sufficient information concerning the management of the financial disaster